Geoinformatics-Based Morphologic Analysis of the Ramis River, an Endorheic Andean River - (:unkn) unknown (Springer Nature Singapore, 2024)
One way to quantify the various morphometric features of a river is through morphology. The North–south-flowing Ramis River is a major tributary of Lake Titicaca, one of the world’s largest lakes. The Ramis has been exhibiting marked changes in its m...
Keywords: Geomorfología fluvial; Río Ramis